Financial derivatives futures, forwards, swaps, options, corporate securities, and credit default swaps - Kōnstantinidēs, Giōrgos 1947- (World Scientific, 2015)
Derivatives markets are an important and growing segment of financial markets and play an important role in the management of risk. This invaluable set of lecture notes is meant to be used in conjunction with a standard textbook on derivatives in an advanced undergraduate or MBA elective course on futures, forwards, swaps, options, corporate securities and credit default swaps. It covers the foundations of derivatives pricing in arbitrage-free markets, develops the methodology of risk-neutral valuation as well as discusses hedging and the management of risk
Keywords: Derivative securities; Options (Finance); Swaps (Finance); Derivat -- Wertpapier